Postoperative pain control for shoulder arthroplasty - Mahala Walker; Srinath Kamineni (Clinics in Shoulder and Elbow)
Since its inception in 1893, shoulder arthroplasty has become an increasingly common surgical procedure. Between 1998 and 2008, shoulder arthroplasty procedures increased by nearly 28,000 cases per year in the United States alone and is the fastest growing joint replacement surgery among all joint. Despite its advantages, shoulder arthroplasty is often accompanied by significant postoperative pain. Pain control continues to be a major concern in patient management, as it impacts operative costs, postoperative mobility, length of hospital stay, patient satisfaction, and overall surgical outcomes. This review aims to provide an overview of drugs such as opioids and regional anesthetics, as well as methods such as local wound infiltration, nerve block, brachial plexus infiltration, cryotherapy and multimodal approaches employed in postoperative shoulder arthroplasty pain control.